Skill Gap Analysis of Extensionists working in Krishi Vigyan Kendras in India - Rohit, Jagriti; Singh, Premlata; Chahal, V P; Satyapriya, Satyapriya (The Indian Journal of Agricultural Sciences, 2020)
Effective and efficient Extensionists are essential for delivering the required services to the farmers. Skill Gap Analysis is important to make the Extensionists updated and competent in their field. A Skill Gap Analysis using Borich Need Assessment Model was carried out in the four zones of Krishi Vigyan Kendras (KVKs) during 2016. The zones of ICAR-KVK were selected using simple random sampling. Twenty KVK from each zone were selected randomly and 3 Extensionists from each KVK were selected by using simple random sampling technique. The total sample size was 240. Mean weighted discrepancy score (MWDS) was used to study the skill gap. The result of the study indicated that the highest level of skill gap were expressed in designing and conducting farmers training, assessing training needs of the farmers, their ability to use computer (internet) and power point presentation, knowledge and awareness to approaches towards adult education and their ability to prepare visual aids to help deliver information. Lowest mean weighted discrepancy score was given to their ability in presenting the seminar and coordinating work with their peer. Inadequate funding emerged as the major barrier in acquiring the required competencies. Attention should be given to skill gap analysis owing to the importance given to skill development at the national level. Extensionists with the required skill in their job will lead to the better performance and ultimately better services to farmers.